Pneumocephalus Following Thoracic Surgery with Posterior Chest Wall Resection - Müller, Ina; Tönnies, Mario; Pfannschmidt, Joachim; Kaiser, Dirk (The Thoracic and Cardiovascular Surgeon Reports, 2015)
Pneumocephalus can be seen after head injury with fracture of the skull-base or in cerebral neoplasm, infection, or after intracranial or spinal surgery. We report on a 69-year-old male patient with pneumocephalus after right-sided lobectomy and en bloc resection of the chest wall for non-small-cell lung cancer. Postoperatively, the patient showed a reduced vigilance level with no response to pain stimuli and anisocoria. The CCT scan revealed an extensive pneumocephalus; following which, the patient underwent neurosurgery with laminectomy and ligature of the transected nerve roots. After operation the patient returned to his baseline mental status.
Keywords: thoracic surgery; chest wall; lung cancer treatment (surgery medical); neurology/neurologic (deficits disease injury)